2020
DOI: 10.1111/zph.12681
|View full text |Cite
|
Sign up to set email alerts
|

The study of seroprevalence of hepatitis E virus and an investigation into the lifestyle behaviours of the aborigines in Malaysia

Abstract: Malaysia is a non‐endemic country for hepatitis E virus (HEV) infection. However, seroprevalence as high as 50% among samples of aboriginal people were reported over two decades ago. A total of 207 samples collected from seven aboriginal villages in rural settlements across two states in Malaysia were analysed for anti‐HEV IgG and IgM by an enzyme‐linked immunoassay. Following the detection of anti‐HEV seroprevalence, we organized health outreach to inform and educate the community. Qualitative interviews were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Over two decades since these studies, there have been no further reports on HEV seroprevalence in Malaysia. A 2019 study found an anti-HEV IgG positive rate of 5.9% in a sample of Orang Asli in the state of Negeri Sembilan [ 22 ]. With the worrisome upward trend in HEV seroprevalence across the world and the fact that transfusion-transmitted HEV can cause serious clinical consequences, this study screened the previously archived blood donor samples in Malaysia for anti-HEV IgM/ IgG to determine an up-to-date seroprevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Over two decades since these studies, there have been no further reports on HEV seroprevalence in Malaysia. A 2019 study found an anti-HEV IgG positive rate of 5.9% in a sample of Orang Asli in the state of Negeri Sembilan [ 22 ]. With the worrisome upward trend in HEV seroprevalence across the world and the fact that transfusion-transmitted HEV can cause serious clinical consequences, this study screened the previously archived blood donor samples in Malaysia for anti-HEV IgM/ IgG to determine an up-to-date seroprevalence.…”
Section: Introductionmentioning
confidence: 99%
“…From April 2011 to February 2013, Wong et al (2020) collected 207 blood samples from healthy aboriginal communities and analyzed for anti-HEV IgG and IgM in 2018 and conducted semi-structured interviews through a cross-sectional study. Usage of river water for daily washing and recreational swimming occasionally or when clean water sources was not available, seems to be one of the major reasons causing HEV infection in the aboriginal villages at Negeri Sembilan and Selangor.…”
Section: Hepatitis and Enterovirusmentioning
confidence: 99%
“…Usage of river water for daily washing and recreational swimming occasionally or when clean water sources was not available, seems to be one of the major reasons causing HEV infection in the aboriginal villages at Negeri Sembilan and Selangor. Participants also claimed that outbreaks of HEV were not uncommon, this could imply that WASH practices and surveillance in the aboriginal communities need to be improved to prevent transmission of HEV (Wong et al, 2020). A cross-sectional study was conducted on 120 university students in Klang Valley to evaluate KAP, which is important to reduce the risk of viral hepatitis infection.…”
Section: Hepatitis and Enterovirusmentioning
confidence: 99%
“…A recent study in 2019 on a relatively large sample of the indigenous population in Malaysia found an anti-HEV IgG positive rate of 5.9%. 26 Most recently, in 2020, HEV-specific IgG antibodies were detected in 3.1% and IgM in 0.9% of blood donor samples in Malaysia. 27 Of note, the prevalence of HEV viraemia varies among global blood donors.…”
Section: Introductionmentioning
confidence: 99%